Real-time optimal switching angle scheme for a cascaded H-Bridge inverter using Bonobo Optimizer - Abdul Wahab, Noor Izzri; Abdulsalam Taha, Taha; Hassan, Mohd Khair; Zaynal, Hussein I.; Taha, Faris Hassan; Mohammed Hashim, Abdulghafor (Universitas Muhammadiyah Yogyakarta, 2024)
This study demonstrates a novel method for using the Bonobo Optimizer (BO) to selective harmonic elimination in a cascaded H-Bridge Multilevel Inverter (CHB-MLI) running on solar power. The primary objective is to calculate, in real time, the optimal switching angles for eliminating low-order harmonics while maintaining a constant output voltage despite variations in the input voltage. To prove that the BO algorithm works, tests were done on a three-phase, seven-level CHB-MLI that compared it to other evolutionary algorithms like the genetic algorithm (GA) and particle Swarm optimization (PSO). An adaptive BO-Artificial neural network (BO-ANN) based system was developed to compute real-time switching angles and applied to a 7-level CHB-MLI. The results demonstrate that the BO algorithm is the most accurate and fastest evolutionary algorithm for calculating optimal switching angles. This study illustrates the BO algorithm's effective utilization in real-time harmonic elimination applications in CHB-MLI.